KUALITAS PELAYANAN KESEHATAN DALAM UPAYA MENURUNKAN KEMATIAN IBU DI PUSKESMAS BIROMARU KABUPATEN SIGI - Santi, Santi (Katalogis, 2016)
This research aims at determining the quality of health care in reducing maternal mortality in Puskesmas Biromaru, Sigi. The method of this researchÂ is descriptive qualitative to obtain in-depth information from the informants. Seven informants were selected by using purposive sampling technique, who are on duty in the clinic of Biromaru, the head of the clinic, doctor, midwife coordinator, executive midwives and pregnant women. Observation and documents analysis were also done to get the needed data. The results show that the quality of health care in reducing maternal mortality in the clinic has not run according to the standards and procedures in charge. Of the five indicators in use, responsiveness, assurance and empathy have already been fulfilled while tangible still needs to be in the reinventoried in respect of the number of lost and damaged facilities and equipments. Similarly, the reliability still needs to be improved further particularly personnel skills, which can be obtained through a tiered education and training or an internship, so that the competence of the personnel can be improvedÂ and effectiveness of the reduction in maternal mortality in the clinic can be achieved.